2017
DOI: 10.4314/jasem.v21i6.5
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation Potentials of Cassava Mill Effluent (CME) by Indigenous Microorganisms

Abstract: ABSTRACT:The indiscriminate discharge of Cassava mill effluent pose serious environmental and public health implications. This work was aimed at assessing the biodegradation potentials of indigenous microbial isolates from cassava mill effluent using screening and shake flask degradation tests. The mean heterotrophic bacterial and fungal counts were 3.4±0.26 x 10 6 cfu/ml and 1.1±0.20 x 10 6 cfu/ml respectively. The microorganisms isolated, characterized and identified include the genus Pseudomonas (15.48%), B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 2 publications
0
7
1
2
Order By: Relevance
“…The faecal coliforms dominated in this study which differs significantly from other similar studies such as that of Enerijiofi et al [23] who obtained Pseudomonas, Bacillus, Acetobacter, Rhizopus, Corynebacterium, Lactobacillus, Micrococcus, Aspergillus, Staphylococcus, Penicillum and Saccharomyces from cassava mill effluent. Pseudomonas and Bacillus dominated.…”
Section: Biological Properties Of Effluent Samplescontrasting
confidence: 97%
See 1 more Smart Citation
“…The faecal coliforms dominated in this study which differs significantly from other similar studies such as that of Enerijiofi et al [23] who obtained Pseudomonas, Bacillus, Acetobacter, Rhizopus, Corynebacterium, Lactobacillus, Micrococcus, Aspergillus, Staphylococcus, Penicillum and Saccharomyces from cassava mill effluent. Pseudomonas and Bacillus dominated.…”
Section: Biological Properties Of Effluent Samplescontrasting
confidence: 97%
“…Cassava processing mills, therefore, traverse the length and breadth of the country. Relatively large volumes of effluent are generated from the different processes required in cassava processing including washing, grating, moisture extraction, sieving and fermentation [23]; Padmaja [24] assert volumes of up to 3.68m 3 ton -1 annually. Cassava processing plants have a high pollution potential due to both the quantity of wastewater produced and its constituents.…”
Section: Introductionmentioning
confidence: 99%
“…The counts were higher in CME-contaminated soil with a concentration of 400 ml than other contaminated soils. Similar investigation attributed the proliferation to bacteria growth, which utilized the organic matter from the CME (Enerijiofi et al, 2017).…”
Section: Ajhse 1(2)mentioning
confidence: 86%
“…Also, the growth of bacterial in the cassava mill contaminated environment could imply that these microbes are utilizing the cassava mill effluents as a medium for growth; thus, implicating the bacteria adapting and subsequently degrading the contaminant (Oviasogie et al, 2014). Enerijiofi et al (2017) reported that cassava mill effluents are rich in organic matters that can be metabolized by microbial enzymes. They also posited that the cassava mill effluents also serve as primary carbon and energy source for the microorganisms.…”
Section: Ajhse 1(2)mentioning
confidence: 99%
See 1 more Smart Citation